Valorization of biomass for food protein via deep eutectic solvent extraction: Understanding the extraction mechanism and impact on protein structure and properties - Hanafi, Mohamad Ariff; Anwar, Farooq; Saari, Nazamid (John Wiley and Sons Inc, 2024)
The conventional techniques for protein extraction from biomass are not fully aligned with sustainability goals, so it is important to look for some alternate solutions. By simultaneously extracting both soluble and insoluble proteins, deep eutectic solvents (DESs) offer a viable method for valorizing protein-rich biomass from a variety of sources. Notably, the molecular crowding effects of DESs may have helped unfolded proteins acquire compact and stable conformations, facilitating solubilization and effective extraction. However, there is still a lack of information regarding how DESs interact with proteins and affect the structure and properties of the recovered proteins. To enable their widespread usage as a sustainable method for extracting dietary proteins, the safety of DES-extracted proteins must also be addressed. In this paper, we review the state of the science in DES-mediated protein extraction, focusing on the extraction mechanism and the interactions between DESs and proteins. Additionally, important aspects of DES-mediated protein extraction that could affect the structure, technofunctional, nutritional characteristics, and safety of extracted protein are explored. DES-based protein extraction could be helpful to valorize different biomasses for the production of food proteins due to the specific features.